Metric Spaces
Lecture Notes and Exercises, Fall 2015
M.van den Berg
School of Mathematics University of Bristol BS8 1TW Bristol, UK mamvdb@bristol.ac.uk
1
Deﬁnition of a metric space.
Let X be a set, X
= ∅. Elements of X will be called points.
Deﬁnition 1.1 (a) A map d : X × X → R is called a metric on X if
(M1) 
(∀(x, y) ∈ X × X) [0 ≤ d(x, y) < ∞] . 

(M2) 
(∀(x, y) ∈ X × X) [(d(x, y) = 0) ⇔ (x = y)] . 

(M3) 
(∀(x, y) ∈ X × X) [d(x, y) = d(y, x)] . 

(M4) 
(∀(x, y, z) 
∈ X × X × X) [d(x, y) ≤ d(x, z) + d(z, y)] . 
(b) (X, d) is called a metric space and d(x, y) is the distance between points x and y.
Remark 1.2 Conditions (M1)(M4) are the axioms of a metric space. (M4) is called the triangle inequality.
Example 1.3 Let X be a nonempty set. Deﬁne d : X ^{2} → R by
d(x, y) =
1,
0,
if
if
x
x = y.
= y,
Then d is a metric on X, and (X, d) is a discrete metric space.
Example 1.4 Let R be the real line with d(x, y) = x − y. Then (R, d) is a metric space.
Example 1.5 
Let X = R ^{N} := {x = (x _{1} , x _{2} , 

deﬁned by 


N 

d(x, y) = 




j=1 
Then (R ^{N} , d) is a metric space.
, x _{N} )  x _{i} ∈ R,
(x _{j} − y _{j} ) ^{2}
1/2
1 ≤ i ≤ N }.
.
Let d : X ^{2} → R be
Theorem 1.6 Let X = l ^{2} := {x = (x _{n} ) _{n}_{∈}_{N}  ^{}
∞
n=1 ^{x}
_{n} 2 < ∞}. Let d : X ^{2} → R be deﬁned
d(x, y) =
Then (l ^{2} , d) is a metric space.
∞
j=1
(x _{j} − y _{j} ) ^{2}
1/2
.
Proof.
Since 0 ≤ (x _{j} − y _{j} ) ^{2} ≤ 2(x
2
j
+ y
2
j
) we have that
0 ≤
∞
j=1
(x _{j} − y _{j} ) ^{2} ≤ 2
∞
j=1
x
2
j
+ 2
∞
j=1
y
2
j
< ∞.
by
This proves (M1). (M2) and (M3) follow immediately from Deﬁnition 1.1. To prove (M4) we let z ∈ ^{2} . Let n ∈ N be arbitrary and let a _{i} = x _{i} − z _{i} , b _{i} = z _{i} − y _{i} . Since
n
i=1
(a _{i} + b _{i} ) ^{2} 1/2 ≤
n
i=1
a
2
i
1/2 +
n
i=1
b
2
i
^{} 1/2
(∗)
we have that
_{}
n
i=1
(x _{i} − y _{i} ) ^{2} 1/2 ≤ d(x, z) + d(z, y).
We obtain (M4) by letting n → ∞. To prove (∗) we note that this equivalent to
n
i=1
a _{i} b _{i} ≤
n
i=1
^{} 1/2 ^{} a i 2
n
i=1
b
2
i
^{} 1/2
.
The above follows directly from the fact that for λ ∈ R
n
i=1
(λa _{i} + b _{i} ) ^{2} = Aλ ^{2} + 2Hλ + B ≥ 0,
where A = ^{} ^{n}
i=1 ^{a} i
2
, B = ^{} ^{n}
i=1 ^{b} i
2
have that H ^{2} ≤ AB.
, H
= ^{} ^{n}
_{i}_{=}_{1}
a _{i} b _{i} . Since the quadratic in λ is nonnegative we ✷
Theorem 1.7 Let X be a nonempty set, and let B (X ) be the set of all bounded realvalued functions from X to R. Deﬁne d : B(X) ^{2} → R by
d(f, g) = sup
x∈X f(x) − g(x).
Then d is a (supremum) metric on B(X).
Proof. 
Since f, g ∈ B(X) there exist constants c _{1} , c _{2} such that f (x) ≤ c _{1} , g(x) ≤ c _{2} on X. 
Then 0 
≤ f (x) − g(x) ≤ f (x) + g(x) ≤ c _{1} + c _{2} . Hence 
0 ≤ sup
x∈X f(x) − g(x) ≤ c _{1} + c _{2} .
This proves (M1). (M2) and (M3) follow immediately from Deﬁnition 1.1. To prove (M4) we let h ∈ B(X). Then there exist c _{3} such that h(x) ≤ c _{3} on X. Hence
f(x) − g(x)
and
≤ f(x) − h(x) + h(x) − g(x) ≤ sup _{x}_{∈}_{X} f (x) − h(x) + sup _{x}_{∈}_{X} h(x) − g(x) = d(f, h) + d(h, g),
x∈X f (x) − g(x) ≤ d(f, h) + d(h, g).
sup
✷
Deﬁnition 1.8 Let (X, d) be a metric space and let Y be a nonempty subset of X. The restriction of d : X × X → R to d : Y × Y → R induces a metric on Y .
Deﬁnition 1.9 (a) Let X be a vector space over R (or C). A mapping

· 

: X 
→ R 

is called a norm if 

(N1) 
(∀x ∈ X) [0 ≤ x < ∞] . 

(N2) 
(∀x ∈ X) [ x = 0 ⇔ x = 0] . 

(N3) 
(∀x ∈ X, ∀λ ∈ R(or C) ) [ λx = λ x ] . 

2 
(N4)
(∀x ∈ X, ∀y ∈ X) [ x + y ≤ x + y ] .
(b) X supplied with a norm is called a normed space.
Proposition 1.10 Let (X, · ) be a normed space. Then X is a metric space with the metric deﬁned by
∀x, y ∈ X d(x, y) = x − y .
Proposition 1.11
Proof.
Hence
By (M4)
∀x, y, z ∈ X
:
d(x, z) − d(y, z) ≤ d(x, y).
d(x, z) ≤ d(x, y) + d(y, z).
d(x, z) − d(y, z) ≤ d(x, y).
By reversing the role of x and y, and by (M3)
d(y, z) − d(x, z) ≤ d(y, x) = d(x, y).
✷ 

Proposition 1.12 

∀x, y, u, v 
∈ 
X 
: d(x, u) 
− d(y, v) ≤ d(x, y) + d(u, v). 

Proof. 

d(x, u) 
≤ 
d(x, y) + d(y, u) ≤ d(x, y) + d(y, v) + d(v, u) 

= 
d(x, y) + d(y, v) + d(u, v) 

⇒ d(x, u) − d(y, v) ≤ d(x, y) + d(u, v). 

By reversing the roles of x and y and of u and v respectively, 

d(y, v) − d(x, u) ≤ d(y, x) + d(v, u) = d(x, y) + d(u, v). 

✷ 
Example 1.13 Let (X _{1} , d _{1} ), (X _{2} , d _{2} ) be metric spaces. Let X = X _{1} ×X _{2} , and deﬁne d : X ^{2} → R by
∀(x _{1} , x _{2} ), (y _{1} , y _{2} ) ∈ X
d((x _{1} , x _{2} ), (y _{1} , y _{2} )) = d ^{2} (x _{1} , y _{1} ) + d _{2} ^{2} (x _{2} , y _{2} ).
1
Then (X, d) is a metric space: the Cartesian product of (X _{1} , d _{1} ) and (X _{2} , d _{2} ).
3
2
Convergence in metric spaces.
Deﬁnition 2.1 Let (X, d) be a metric space. A sequence of points x _{1} , x _{2} , X is convergent if there is an element x ∈ X such that
We write
lim
_{n}_{→}_{∞} x _{n} = x or x _{n} → x.
_{n}_{→}_{∞} d(x _{n} , x) = 0.
lim
(shorthand (x _{n} ))in
Example 2.2 Let (R ^{N} , d) be the standard Euclidean space. Then
x ^{(}^{n}^{)} = (x
(n)
1
,
.
.
. , x
(n)
N
) → x = (x _{1} ,
, x _{N} ) if and only if x
(n) → x _{j} for all 1 ≤ j ≤ N .
j
Proof.
N
(x
j=1
1/2
≤
N
j=1
d((x
Also for j = 1,
(n)
1
,
.
.
, N
. , x
(n)
N
), (x _{1} ,
, x _{N} )) =
x
(n)
j
(n)
j
−
x _{j} ) ^{2}
x
(n)
j
^{−}
x _{j} . 

✷ 

: 
X 
→ Y , be a 
−
x _{j}  ≤ d(x ^{(}^{n}^{)} , x).
Deﬁnition 2.3 Let X be a set and let (Y, d) be a metric space.
sequence of functions. Then (f _{n} ) converges pointwise if there exists a function f : X → Y such that
Let (f _{n} ), f _{n}
(∀x ∈ X) [ lim
_{n}_{→}_{∞} d(f _{n} (x), f (x)) = 0].
(f _{n} ) converges uniformly if there exists a function f : X → Y such that
or
lim
n→∞
(∀ε > 0) (∃N ∈ N)
sup
x∈X d(f _{n} (x), f (x)) = 0,
^{} (n ≥ N ) =⇒ sup
x∈X d(f _{n} (x), f (x)) < ε ^{} .
Remark 2.4 Uniform convergence implies pointwise convergence. The converse need not be true. Convergence of a sequence of (f _{n} ), f _{n} ∈ B(X), n = 1, 2, · · · with the supremum metric is nothing but uniform convergence.
Example 2.5
1. However, (f _{n} ) does not converge uniformly since
Let f _{n} : (0, 1) → R, f _{n} (x) = x ^{n} . Then f _{n} → f
x∈(0,1) f _{n} (x) − f (x) =
sup
x∈(0,1) f ^{n} (x) =
sup
pointwise, where f (x) = 0, 0 < x <
sup
x∈(0,1)
x ^{n} = 1.
Let f _{n} : [0, ∞) → R,
f _{n} (x) =
_{n}_{+}_{x} . Then f _{n} → f pointwise, where f (x) = x, x ≥ 0. However,
nx
(f _{n} ) does not converge uniformly since
f n ^{n}
2
− f ^{n}
2
_{} = ^{n} _{6} → ∞.
Let f _{n} : [0, ∞) → R,
f _{n} (x) =
converges uniformly to f since
^{n}^{x} _{2} _{x} .
1+n
Then f _{n} → f
pointwise, where f (x) = 0, x ≥ 0. (f _{n} )
x∈[0,∞) f _{n} (x) − f(x) ≤
sup
1
n ^{.}
4
Let f _{n} : [0, 1] → R be given by
f _{n} (x) =
1
n ^{2} + x ^{2} ^{.}
Then f _{n} → 0 in B[0, 1] with the supremum metric.
x∈[0,1] f _{n} (x) − 0 =
sup
sup
x∈[0,1]
Let g _{n} : [0, 1] → R be given by
g _{n} (x) =
1 1
n ^{2} + x ^{2} ^{≤} n ^{2}
2nx
1 + n ^{2} x ^{2} ^{.}
→ 0 (n → ∞)
Then g _{n} does not converge in B[0, 1] with the supremum metric. g _{n} (x) → 0 for every x ∈ [0, 1]. But:
x∈[0,1] g _{n} (x) − 0 = 1
sup
= 0.
Theorem 2.6 Let (X, ρ), (Y, d) be metric spaces, and let f _{n} : X → Y, f _{n} → f converge uniformly on X. If c is a point at which each f _{n} is continuous, then f is continuous at c.
Proof. Let N ∈ N be such that n ≥ N implies sup _{x}_{∈}_{X} d(f _{n} (x), f (x)) <
ρ(c, x) < δ implies d(f _{N} (x), f _{N} (c)) <
_{3} ε . Then for ρ(c, x) < δ
_{3} ε . Let δ be such that
d(f (c), f (x)) ≤ d(f (c), f _{N} (c)) + d(f _{N} (c), f _{N} (x)) + d(f _{N} (x), f (x)) < ε
Hence f is continuous at c.
✷
Deﬁnition 2.7 Let f _{n} :
R, if the partial sums s _{n} = f _{1} + ··· + f _{n} converge uniformly to s.
X → R, n = 1, 2,
∞
Then ^{} _{n}_{=}_{1} f _{n} converges uniformly to s, s : X →
∞
Theorem 2.8 If the series ^{} _{n}_{=}_{1} f _{n} of realvalued functions converges uniformly to s, and if each f _{n} is continuous at c then s is continuous at c.
Proof.
s _{n} = f _{1} + ··· + f _{n} is continuous at c. The result follows by Theorem 2.6
✷
Example 2.9 ^{} _{n}_{=}_{1} x ^{n} converges pointwise on (−1, 1) to s(x) =
Hence sup _{x}_{∈}_{(}_{−}_{1}_{,}_{1}_{)} s _{n} (x) − s(x) = sup _{x}_{∈}_{(}_{−}_{1}_{,}_{1}_{)}  ^{x} ^{n}^{+}^{1}  ≥ gence is not uniform.
∞
_{1}_{−}_{x} . Note that s _{n} (x) = ^{1}^{−}^{x} ^{n}^{+}^{1}
1
^{.}
_{2} , and the conver
1−x
1
1
_{2} ^{s}^{u}^{p} x∈(−1,1) ^{}^{x}^{} ^{n}^{+}^{1} ^{=}
1−x
Example 2.10 Let f _{n} : [0.1] → R, f _{n} (x) = nxe ^{−}^{n}^{x} ^{2} .
function which is 0 on [0, 1].
Then (f _{n} ) converges pointwise to the
Note that
1 _{n} ) ≥
The convergence is not uniform since f _{n} (
as n → ∞, and so ^{}
√
0
f _{n} (x)dx = ^{1}
1
_{2} (1 − e ^{−}^{n} ) →
_{2}
1
0
f _{n} (x)dx
1
→ ^{}
0
1
0dx.
Theorem 2.11 Let f _{n} : [a, b] → R, n = 1, 2,
which converges uniformly to f on [a, b].
be a sequence of Riemann integrable functions
b f _{n} (x)dx →
Then f is Riemann integrable, and ^{}
a
a
f (x)dx.
b
Proof. For each ε > 0 there exists N ∈ N such that n ≥ N, x ∈ [a, b] implies f _{n} (x) − f (x) < ε. Hence for any partition P of [a, b], and for n ≥ N
U(P, f) ≤ U(P, f _{n} ) + ε(b − a), L(P, f) ≥ L(P, f _{n} ) − ε(b − a).
5
Since f _{N} is Riemann integrable, there exists a partition P of [a, b] such that U ( P, f _{N} )−L( P, f _{N} ) < ε. Then
U( P, f) − L( P, f)
< U( P, f _{N} ) + (b − a) − L( P, f _{N} ) + ε(b − a) < ε(1 + 2(b − a)).
Since ε > 0 was arbitrary, f is Riemann integrable. Hence for n ≥ N
a
b
f (x)dx
=
inf{U (P, f ) : P a partition of [a, b]}
≤ inf{U (P, f _{n} ) : P a partition of [a, b]} + ε(b − a)
Similarly, for n ≥ N
=
_{}
a
b
a
b
f _{n} (x)dx + ε(b − a).
f (x)dx ≥
a
b
f _{n} (x)dx − ε(b − a).
Combining these two inequalities we have for n ≥ N

a
b
f (x)dx −
a
b
f _{n} (x)dx ≤ 2ε(b − a).
✷
Remark 2.12 Let f _{n} : [0, ∞) → R, f _{n} (x) =
∞ f _{n} (x)dx = 1.
function on [0, ∞). However, ^{}
0
_{n} 1 e ^{−}^{x}^{/}^{n} .
Then (f _{n} ) converges uniformly to the 0
Remark 2.13 If f _{n} → f pointwise on [a, b], and f _{n} is Riemann integrable for all n ∈ N. Then f
} be an enumeration of the rationals
f _{n} (x)dx =
in [0, 1], f _{n} (x) =
need not to be Riemann integrable. For example, let {q _{1} , q _{2}
1,
0,
x ∈ {q _{1} , otherwise.
,
q _{n} },
1
Then f _{n} is Riemann integrable with ^{}
0
0, f _{n} → f pointwise with f (x) =
But U (P, f ) = 1, L(P, f ) = 0, and f is not Riemann integrable.
1,
0,
Q ∩ [0, 1]
x
x ∈ [0, 1] Q.
∈
Corollary 2.14 If ^{} _{n}_{=}_{1} f _{n} converges uniformly to s on [a, b], and if each f _{n} is Riemann inte
grable on [a, b]. Then s is integrable, and ^{}
∞
a
s(x)dx = ^{}
b
∞
n=1 a
b
f _{n} (x)dx.
Proof.
= lim _{n}_{→}_{∞} ^{} ^{n}
Put s _{n} = f _{1} + ··· + f _{n} . Then ^{}
a
b
k=1 a
f _{k} (x)dx = ^{}
∞
k=1 a
b
s(x)dx = lim _{n}_{→}_{∞} ^{}
a
f _{k} (x)dx.
b
b
s _{n} (x)dx
✷
Theorem 2.15 Let (f _{n} ) be a sequence of realvalued diﬀerentiable functions on [a, b]. Suppose that (f _{n} (x)) converges for at least one x ∈ [a, b], and that f _{n} converges uniformly on [a, b]. Then (i) f _{n} converges uniformly on [a, b], (ii) f = lim _{n}_{→}_{∞} f _{n} is diﬀerentiable on [a, b], and for all x ∈ [a, b], f ^{} (x) = lim _{n}_{→}_{∞} f _{n} (x).
Proof. Let lim _{n}_{→}_{∞} f _{n} = g, and let ε > 0. Since (f _{n} ) converges uniformly on [a, b], there exists
N
m,
∈ N such that sup _{a}_{≤}_{x}_{≤}_{b} f _{n} (x) − g(x) < ε for n ≥ N . Hence sup _{a}_{≤}_{x}_{≤}_{b} f _{n} (x) − f _{m} (x) ≤ 2ε for
n ≥ N . If ξ _{1} , ξ _{2} are points of [a, b] then, by the mean value theorem for f _{n} − f _{m}
f _{n} (ξ _{1} ) − f _{m} (ξ _{1} ) − (f _{n} (ξ _{2} ) − f _{m} (ξ _{2} )) = (ξ _{1} − ξ _{2} ).{f _{n} (ξ) − f _{m} (ξ)}
where ξ ∈ [ξ _{1} , ξ _{2} ]. So for all m, n ≥ N ,
(1)
f _{n} (ξ _{1} ) − f _{m} (ξ _{1} ) − (f _{n} (ξ _{2} ) − f _{m} (ξ _{2} )) ≤ 2ξ _{1} − ξ _{2} ε.
6
If x _{0} is a point for which (f _{n} (x _{0} )) converges, then there is an N ^{} ∈ N such that for m, n ≥ N ^{}
(2)
f _{n} (x _{0} ) − f _{m} (x _{0} ) ≤ ε.
Let x be any point of [a, b]. By (1), (2) with ξ _{1} = x, ξ _{2} = x _{0} we have for m, n ≥ max{N, N ^{} },
(3)
f _{n} (x) − f _{m} (x) ≤ (1 + 2x − x _{0} )ε ≤ (1 + 2(b − a))ε.
Hence lim _{m}_{→}_{∞} f _{m} (x) exists for all x ∈ [a, b]. Taking the limit m → ∞ in (3) we see that (f _{n} )
converges uniformly on [a, b]. Let a < c < b, and let h
By (1) with ξ _{1} = c + h, ξ _{2} = c we have for m, n ≥ N
= 0 be such that c + h ∈ [a, b].
f _{n} (c + h) − f _{n} (c)
_{−} f _{m} (c + h) − f _{m} (c)
h
h
_{} ≤ 2ε.
Since f _{m} (c + h) − f _{m} (c) → f (c + h) − f (c) as m → ∞, the above inequality shows that for n ≥ N
f _{n} (c + h) − f _{n} (c)
_{−} f(c + h) − f(c)
h
h
_{} ≤ 2ε.
By the deﬁnition of the derivative f _{N} (c) there exists on δ > 0 such that
(0 < h ≤ δ) =⇒ ^{}
f _{N} (c + h) − f _{N} (c)
h
− f _{N} (c) _{} ≤ ε .
Then for 0 < h ≤ δ
f(c + h) − f(c)
h
− g(c)
− f _{N} (c) _{}
^{≤}
f _{N} (c + h) − f _{N} (c)
+
h
Hence f ^{} (c) exists and f ^{} (c) = lim _{n}_{→}_{∞} f _{n} (c).
+
f(c + h) − f(c)
_{−} f _{N} (c + h) − f _{N} (c)
h
h
f _{N} (c) − g(c) ≤ 2ε + ε + ε.
Corollary 2.16 Let u _{n} : [a, b] → R be such that
(i) (∃x _{0} ∈ [a, b])
n=1
∞
u _{n} (x _{0} ) is convergent .
(ii) (∀n ∈ N) u _{n} is diﬀerentiable.
(iii) The series
∞
n=1
u _{n} (x) is uniformly convergent on [a, b].
Then the series
_{∞}
n=1
u _{n} (x)
converges uniformly to s(x) and
s ^{} (x) =
∞
n=1
u _{n} (x).
✷
Theorem 2.17 
If x _{n} → x in (X, d) and x _{n} → y in (X, d) then x = y. 
Proof. 
0 ≤ d(x, y) ≤ d(x, x _{n} ) + d(x _{n} , y) → 0
7
=⇒ x = y.
✷
Theorem 2.18 Let x _{n} → x and y _{n} → y in (X, d). Then d(x _{n} , y _{n} ) → d(x, y).
Proof.
0 ≤ d(x _{n} , y _{n} ) − d(x, y) ≤ d(x, x _{n} ) + d(y _{n} , y) → 0.
✷
Deﬁnition 2.19 Let (X, d) and (X, e) be metric spaces. The metrics d and e are equivalent if
d(x _{n} , x) → 0 ⇐⇒ e(x _{n} , x) → 0.
Remark 2.20 If there are c _{1} , c _{2} > 0 such that
∀x, y ∈ X
then d and e are equivalent.
c _{1} d(x, y) ≤ e(x, y) ≤ c _{2} d(x, y)
Example 2.21 On R ^{2}
and
are equivalent.
d((x _{1} , y _{1} ), (x _{2} , y _{2} )) = ^{} (x _{1} − x _{2} ) ^{2} + (y _{1} − y _{2} ) ^{2}
e((x _{1} , y _{1} ),
(x _{2} , y _{2} )) = x _{1} − x _{2}  + y _{1} − y _{2} 
Proof.
1
√ 2 e((x _{1} , y _{1} ), (x _{2} , y _{2} ))
≤ d((x _{1} , y _{1} ), (x _{2} , y _{2} )) ≤ e((x _{1} , y _{1} ), (x _{2} , y _{2} )).
✷
3 Limit points, open sets, closed sets
Let (X, d) be a metric space, x _{0} ∈ X, r > 0.
Deﬁnition 3.1 The set B(x _{0} ; r) = {x ∈ X
radius r.
:
d(x, x _{0} ) < r} is the open ball with center x _{0} and
B(x _{0} ; r) = {x ∈ X
: d(x, x _{0} ) ≤ r} is the closed ball with center x _{0} and radius r.
Example 3.2 Let R ^{1} have its usual metric, a ∈ R ^{1} . Then B(a; r) = (a − r, a + r),
B(a; r) = [a − r, a + r]. Similarly for R ^{n} , a ∈ R ^{n} ,
r ^{2} }, B(a; r) = {(
Mult mai mult decât documente.
Descoperiți tot ce are Scribd de oferit, inclusiv cărți și cărți audio de la editori majori.
Anulați oricând.